POROSITY AND PERMEABILITY VARIATIONS IN A TIGHT GAS SANDSTONE RESERVOIR ANALOGUE, WESTPHALIAN D, LOWER SAXONY BASIN, NW GERMANY: INFLUENCE OF DEPOSITIONAL SETTING AND DIAGENESIS. (19th September 2017) - Becker, I.; Wüstefeld, P.; Koehrer, B.; Felder, M.; Hilgers, C.
Abstract : Understanding the spatial variability of reservoir properties in tight gas sandstones can significantly reduce uncertainties in reservoir characterization. This study focuses on two outcrops of Upper Carboniferous (Westphalian D) fluvial sandstones in the southern part of the Lower Saxony Basin, NW Germany, which are analogues for tight, gas‐producing reservoir rocks at fields in the north of the basin. Large‐scale differences in reservoir quality occur between the two outcrops which are separated by a distance of approximately 15 km and by 600 m of stratigraphy. Smaller‐scale heterogeneities in the form of channel geometries occur within individual fluvial cycles, as evidenced in a 30 m (high) by 150 m (long) porosity‐permeability profile at one of the outcrops studied. In the Woitzel quarry, lower Westphalian D deposits consist of fining‐upwards cycles of channel and bar sandstones with intercalated floodplain sediments and coal seams. In abandoned quarries at the Hüggel location, upper Westphalian D strata are composed of grey and red coloured sandstones which suggest deposition in a fluvial – alluvial plain environment under increasingly arid conditions. Reservoir quality is higher in the upper Westphalian D sandstones at Hüggel (permeability: up to 1 mD; mean porosity: 19%) than in the lower Westphalian D sandstones at Woitzel (permeability: <0.1 mD; mean porosity: 15%). Due to the high degree of compaction of the upper and lower Westphalian D deposits (intergranular volumes of 21.9% and 19.4% respectively) and the high proportions of pseudomatrix, porosity in these sandstones is mainly secondary with up to 80% microporosity. Reservoir quality is in general higher in the upper Westphalian D sandstones where kaolinite is present. In contrast, intense illitization has degraded the reservoir quality of the lower Westphalian D sandstones. A positive correlation between permeability and grain size is exhibited by the kaolinite‐bearing upper Westphalian D sandstones. No such correlation is evident in the illite‐bearing lower Westphalian D sandstones, unless samples with permeabilities of <0.01 mD are excluded from the correlation. However, such a low permeability cut‐off is not related to sorting, grain size or authigenic quartz cementation. At a small scale, permeability varies laterally by two orders of magnitude from 0.001 mD to 0.1 mD in a single, approximately 3 m thick tight sandstone bed over a distance of 150 m. Repeated, centimetre‐scaled fining‐upwards grading and bed‐internal erosion contribute to lateral variations in reservoir flow characteristics. Integrated studies of the depositional environment, diagenesis and sedimentary geometries of the deposited units are a key to the understanding of heterogeneities in tight fluvial sandstones and thus to the successful development of Upper Carboniferous reservoirs in the Lower Saxony Basin and elsewhere.